Spokane Paper - Influence of Top-Lag on the Depth of the Pipe in Steel Ingots - Henry M. Howe (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1910)
In my original paper, Piping and Segregation in Steel Ingots, I pointed out1 among other things that, in view of the slighter stretching (virtual expansion) of the crust, and greater opportunity for sagging, there should be less piping in broad than in narrow ingots, and less in slowly-cooled ingots, e.g., those cast in pre-heated sand molds, than in those which cool quickly, e.g., those cast in iron molds. A. A. Stevenson said that neither of these predictions agreed with his own experience. In particular, in a picture which he showed of a wide and of a narrow ingot cast from the same ladleful of steel: the wide ingot had certainly piped much more deeply than the narrow one. At the time I did not see the explanation of these discrepancies, but further reflection makes it evident. One of the most important elements in determining the depth of the pipe is the degree of " top-lag," that is, the degree to which the solidification of the top of the ingot lags behind that of the bottom. Through this lagging the steel of the upper part of the ingot is able to run down and fill the pipe below as fast as it forms. To the importance of this lagging I called attention in my original paper.' Sand us. Iron Molds.—If we compare two like ingots, one cast in an iron and the other in a sand mold, we see that the top-lag is much greater in the former than in the latter, because in the former the lower part of the ingot is cooling off fast while the metal is running into the upper part. It is perhaps easier to look at this as a case of the solidification of the hot-